Interactive Ethnomathematics-Based Learning Media: Development of Articulate Storyline 3 to Improve Mathematical Communication Skills - Azin Taufik; Anggar Titis Prayitno; Ahmat Wakit; Wulan Sutriyani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2026)
Mathematical communication skills are essential for critical thinking and conceptual understanding, yet they remain low among students, particularly in connecting mathematics to real-life contexts. This study aims to develop interactive ethnomathematics-based learning media using Articulate Storyline 3 and to examine its feasibility and potential in improving students’ mathematical communication skills. The novelty of this study lies in integrating local cultural contexts from Kuningan Regency into interactive digital media designed specifically to facilitate mathematical communication. This research employed an R&D approach with the ADDIE model (analysis, design, development, implementation, evaluation). The subjects were 23 tenth-grade students of MAN 1 Kuningan. Instruments included expert validation sheets, mathematical communication tests, and response questionnaires. Expert validation showed very high feasibility: material experts 93.21% and media experts 96.92%. Practicality was also very high: student responses 92.85% and teacher responses 96.66%. Effectiveness was demonstrated by an average N-Gain of 0.55 (medium category). The highest improvement occurred in explaining calculation results in written form (N-Gain 0.78, high category), while conveying mathematical contexts and explaining concepts achieved N-Gains of 0.52 and 0.50 (medium category). The main contribution is empirical evidence that integrating ethnomathematics into Articulate Storyline 3 media can be effectively designed, validated, and implemented to improve mathematical communication skills, while offering a contextual media development model adaptable to other local cultures. These findings confirm that interactive ethnomathematics-based learning media are feasible, practical, and effective as an innovative alternative to strengthen students’ mathematical communication skills.